A cyclic sulfonium additive complexing polybromide ion, electrolyte, positive plate and high-rate aqueous zinc-bromine battery thereof

CN122843372APending Publication Date: 2026-09-29GUANGDONG UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611279917.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-21
Publication Date
2026-09-29

AI Technical Summary

Technical Problem

[0006]虽然也有研究者尝试通过隔膜改性、锌负极包覆、正极结构设计等路径缓解上述问题,但这类方案大多存在制备工艺复杂、生产成本偏高的缺陷,且往往仅能改善单一问题,无法同时兼顾多溴离子锚定、电极界面优化、反应动力学提升多重效果,很难满足大规模储能场景下锌溴电池长循环高倍率运行的实际需求

Benefits of technology

[0028]1.本发明提供的技术方案环状锍类络合剂可在电池充放电循环过程中依靠静电吸附作用稳定束缚电解液中的多溴离子,有效抑制多溴化物穿梭效应,避免活性溴组分跨隔膜迁移腐蚀锌负极,减少锌负极枝晶、钝化等副反应,长效保护电池正负极,大幅延长锌溴静态电池循环使用寿命。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122843372A_ABST
    Figure CN122843372A_ABST
Patent Text Reader

Abstract

The application discloses a kind of complexing polybromide cyclic sulfonium additives, electrolyte, positive plate and its high rate water series zinc bromine battery, to provide a kind of complexing polybromide cyclic sulfonium additives, the cyclic sulfonium additives can be used as electrolyte additive, also can be used as positive plate, can simultaneously solve the problem of polybromide shuttle corrosion, slow kinetics and zinc negative electrode interface instability in zinc bromine high rate battery;The cyclic sulfonium additive is cyclic sulfonium bromide salt;With formula 1 structure general formula:;Formula 1 wherein, R is one of methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl;The application also discloses the positive plate, electrolyte and zinc bromine battery containing the complexing polybromide cyclic sulfonium additive;Belongs to the technical field of electrochemical cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application discloses a cyclic sulfonium additive, specifically a cyclic sulfonium additive that complexes polybrominates. This application also discloses a method for preparing the cyclic sulfonium additive that complexes polybrominates and a battery thereof, belonging to the field of electrochemical battery technology. Background Technology

[0002] Electrochemical energy storage has developed rapidly in recent years. Among them, lithium-ion batteries, with their significant advantages such as high operating voltage, high energy density, and no memory effect, have become the focus of research in the field of electrochemical energy conversion and storage. However, problems such as lithium resource shortage and the flammability and explosiveness of organic electrolytes have prompted the academic community to seek alternative technologies. Therefore, safe and reliable aqueous zinc-ion rechargeable batteries are attracting increasing attention.

[0003] In recent years, aqueous zinc-bromine static batteries have emerged as a highly promising energy storage system due to their excellent electrochemical performance and high safety. Zinc anodes are abundant and exhibit excellent electrochemical stability, allowing for stable operation in moderately to weakly acidic electrolytes. Bromine cathodes possess unique advantages such as multi-electron reactions, high theoretical capacity, and readily available and inexpensive raw materials. Compared to organic electrolytes in lithium-ion batteries, aqueous electrolytes offer higher conductivity and are non-toxic and flame-retardant, making this battery suitable for future large-scale energy storage scenarios.

[0004] However, the zinc anode of zinc-bromine batteries is prone to hydrogen evolution and passivation in the electrolyte, and the concentration difference at the interface induces the growth of zinc dendrites. At the same time, the polybromine ions generated during charging and discharging can cause severe shuttle and lead to self-corrosion of the anode, resulting in loss of active materials and rapid capacity decay at high rates, thus making it difficult for zinc-bromine batteries to be used in large-scale energy storage applications.

[0005] Therefore, developing a functional material that can simultaneously solve the problems of polybrominated ion shuttle corrosion, effective confinement of polybrominated ions, slow reaction kinetics, and instability of the zinc anode interface, thereby improving the cycle stability of aqueous zinc-bromine batteries under high-rate conditions, has become a key technical problem that urgently needs to be solved in this field.

[0006] Although some researchers have tried to alleviate the above problems through methods such as membrane modification, zinc anode coating, and cathode structure design, most of these solutions have the drawbacks of complex preparation processes and high production costs. Moreover, they can often only improve a single problem and cannot simultaneously achieve multiple effects such as polybromination anchoring, electrode interface optimization, and improved reaction kinetics. It is difficult to meet the actual needs of long-cycle, high-rate operation of zinc-bromine batteries in large-scale energy storage scenarios.

[0007] Therefore, there is an urgent need to develop a new type of functional additive to improve the cycle stability and rate performance of zinc-bromine batteries and promote the industrial application of high-rate aqueous zinc-bromine batteries. Summary of the Invention

[0008] To overcome the shortcomings of the prior art, the first objective of this invention is to provide a cyclic sulfonium additive that complexes polybrominates. This cyclic sulfonium additive can be used as both an electrolyte additive and a positive electrode, and can simultaneously solve the problems of polybrominate shuttle corrosion, slow kinetics, and unstable zinc anode interface in high-rate zinc-bromine batteries.

[0009] A second objective of the present invention is to provide an electrolyte comprising the cyclic sulfonium additive, which can effectively bind polybrominated ions with the aid of the cyclic sulfonium additive, while adsorbing them onto the zinc anode to increase its interfacial stability.

[0010] A third object of the present invention is to provide a positive electrode comprising the cyclic matte additive.

[0011] The fourth objective of this invention is to provide a high-rate aqueous zinc-bromine battery comprising the above-mentioned electrolyte and positive electrode, which has excellent high-rate discharge performance and long-term cycle stability.

[0012] Therefore, the first technical solution provided by this invention is as follows:

[0013] A cyclic sulfonium additive that complexes polybrominates, wherein the cyclic sulfonium additive is a cyclic sulfonium bromide salt having the general structural formula of Formula 1:

[0014] ;

[0015] Formula 1

[0016] Wherein: R is one of methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, and decyl.

[0017] The second technical solution provided by the present invention is an electrolyte comprising the above-mentioned cyclic sulfonium additive that complexes polybrominates.

[0018] Furthermore, the aforementioned electrolyte also includes soluble zinc salt and water.

[0019] Furthermore, in the aforementioned electrolyte, the soluble zinc salt is at least one selected from zinc sulfate, zinc bromide, zinc chloride, zinc nitrate, zinc oxalate, zinc acetate, zinc fluoride, and zinc trifluoromethanesulfonate.

[0020] Furthermore, in the aforementioned electrolyte, the concentration of the cyclic sulfonium bromide salt is 0.05–0.2 mol / L, and the concentration of the soluble zinc salt is 0.5–1 mol / L.

[0021] The third technical solution provided by the present invention is a positive electrode sheet comprising the above-mentioned cyclic sulfonium additive that complexes polybrominates.

[0022] Furthermore, the aforementioned positive electrode also includes conductive carbon and a binder;

[0023] The conductive carbon is at least one of Super P, Ketjen Black, and acetylene black;

[0024] The adhesive is at least one of carboxymethyl cellulose (CMC), polyvinylidene fluoride (PVDF), and polytetrafluoroethylene (PTFE).

[0025] The present invention also discloses a high-rate aqueous zinc-bromine battery, comprising the above-mentioned electrolyte, positive electrode and negative electrode.

[0026] Furthermore, in the aforementioned high-rate aqueous zinc-bromine battery, the negative electrode is a zinc metal sheet.

[0027] Compared with the prior art, the technical solution provided by the present invention has the following technical advantages:

[0028] 1. The cyclic matte complexing agent provided by this invention can stabilize and bind polybrominated ions in the electrolyte by electrostatic adsorption during battery charge and discharge cycles, effectively suppress the polybrominated shuttle effect, prevent active bromine components from migrating across the separator and corroding the zinc anode, reduce side reactions such as dendrite formation and passivation of the zinc anode, provide long-term protection for the positive and negative electrodes of the battery, and significantly extend the cycle life of the zinc-bromine static battery.

[0029] 2. The technical solution provided by this invention applies an electrolyte composite modified cathode containing cyclic sulfonium additives to an aqueous zinc-bromine static battery system. The cyclic sulfonium groups can optimize the kinetics of bromine redox reaction, accelerate the rate of bromide ion redox reaction, and significantly improve the battery's rate charge-discharge performance at 250 mA / cm². 2 It has a discharge plateau of 1.4V under high current.

[0030] 3. This invention constructs an aqueous zinc-bromine static battery by simultaneously introducing cyclic sulfonium bromide into both the electrolyte and the cathode system. This dual synergistic complexation fixes polybrominated active materials, which not only significantly improves the battery's long-cycle stability and extends its cycle life, but also suppresses side reactions, ensuring that the battery maintains a high and stable coulombic efficiency of 99.15% throughout the entire cycle range and reduces the capacity decay rate.

[0031] 4. The aqueous electrolyte and cyclic sulfite additives of this invention use economical salts, have low additive concentrations, and involve simple processes and mild reaction conditions for preparing the electrolyte and positive electrode. They are easy to prepare and store in large quantities and have good application and development prospects. Attached Figure Description

[0032] Figure 1 The 1H NMR spectrum of methyltetrahydrothiophene sulfonium bromide prepared in Example 1.

[0033] Figure 2 The 1H NMR spectrum of ethyltetrahydrothiophene sulfonium bromide prepared in Example 2 is shown.

[0034] Figure 3 The 1H NMR spectrum of propyltetrahydrothiophene sulfonium bromide prepared in Example 3 is shown.

[0035] Figure 4 Full cells assembled using ethyltetrahydrothiophene sulfonium bromide material have a performance of 10–250 mA / cm². 2 Rate performance diagram at current density.

[0036] Figure 5 Cyclic voltammetry curves of full cells assembled with methyltetrahydrothiophene sulfonium bromide material at a scan rate of 0.2 mV / s.

[0037] Figure 6 Cyclic voltammetry curves of full cells assembled using ethyltetrahydrothiophene sulfonium bromide material at a scan rate of 0.2 mV / s.

[0038] Figure 7 Cyclic voltammetry curves of full cells assembled with propyltetrahydrothiophene sulfonium bromide material at a scan rate of 0.2 mV / s.

[0039] Figure 8 A full cell assembled using methyltetrahydrothiophene sulfonium bromide material achieved a performance of 1 mAh / cm². 2 20 mA / cm 2 The charge / discharge curves are shown below.

[0040] Figure 9 A full cell assembled using ethyltetrahydrothiophene sulfonium bromide material achieved a performance of 1 mAh / cm². 2 20 mA / cm 2 The charge / discharge curves are shown below.

[0041] Figure 10 A full cell assembled using propyltetrahydrothiophene sulfonium bromide material achieved a performance of 1 mAh / cm². 2 20 mA / cm 2 The charge / discharge curves are shown below.

[0042] Figure 11 A comparison of long-cycle coulombic efficiencies of full cells assembled from methyltetrahydrothiophene sulfonium bromide, ethyltetrahydrothiophene sulfonium bromide, and propyltetrahydrothiophene sulfonium bromide materials.

[0043] Figure 12 Full cells assembled with electrolyte and positive electrode containing ethyltetrahydrothiophene bromide material, electrolyte containing ethyltetrahydrothiophene bromide and pure carbon positive electrode, and electrolyte without ethyltetrahydrothiophene bromide and ethyltetrahydrothiophene bromide and positive electrode, have a performance of 1 mAh / cm². 2 20 mA / cm2 A comparison chart of long-cycle coulomb efficiency. Detailed Implementation

[0044] The specific embodiments of the present invention will be further described below. It should be noted that these descriptions are for the purpose of aiding understanding the present invention, but do not constitute a limitation thereof. Furthermore, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0045] Unless otherwise specified, the experimental methods used in the following embodiments are conventional methods, and the experimental materials used in the following embodiments can be purchased through conventional commercial channels unless otherwise specified.

[0046] Example 1

[0047] This embodiment provides a cyclic sulfonium additive that complexes polybrominates, which is prepared by the following steps: 10 mL of tetrahydrothiophene is added to a 250 mL reagent bottle, followed by 50 mL of anhydrous acetone. Then, 10 mL of methyl bromide is added under ice bath conditions, and the mixture is stirred at room temperature for 24 h. After the reaction is complete, anhydrous diethyl ether is added to the reaction solution, resulting in a large amount of white precipitate. The precipitate is centrifuged and repeatedly washed with diethyl ether to obtain a white solid. This solid is then dried under vacuum at 60 °C and -0.1 MPa to obtain the target product, methyltetrahydrothiophene sulfonium bromide. Its 1H NMR spectrum is shown in the figure. Figure 1 ,pass Figure 1 As can be seen, the product synthesized in this embodiment has no other impurity peaks and the product has high purity.

[0048] Example 2

[0049] This embodiment provides a cyclic sulfonium additive that complexes polybrominates, which is prepared by the following steps: 10 mL of tetrahydrothiophene is added to a 250 mL reagent bottle, followed by 50 mL of anhydrous acetone and 10 mL of bromoethane. The mixture is stirred at room temperature for 120 h. After the reaction is complete, anhydrous diethyl ether is added to the reaction solution, resulting in a white precipitate. The precipitate is centrifuged and repeatedly washed with diethyl ether to obtain a white solid. This solid is then dried under vacuum at 60 °C and -0.1 MPa to obtain the target product, ethyltetrahydrothiophene sulfonium bromide. Its 1H NMR spectrum is shown in the figure. Figure 2 ,pass Figure 2 As can be seen, the product synthesized in this embodiment has no other impurity peaks and the product has high purity.

[0050] Example 3

[0051] This embodiment provides a cyclic sulfonium additive that complexes polybrominates, which is prepared by the following steps: 10 mL of tetrahydrothiophene is added to a 250 mL reagent bottle, followed by 50 mL of anhydrous acetone and 10 mL of n-propane bromide. The mixture is stirred at room temperature for 168 h. After the reaction is complete, 200 mL of anhydrous diethyl ether is added to the reaction solution, and the mixture is frozen at -5 °C for 12 h. A white precipitate is formed. After centrifugation, the precipitate is washed repeatedly with diethyl ether to obtain a white solid. This solid is then dried under vacuum at 60 °C and -0.1 MPa to obtain the target product, propyltetrahydrothiophene sulfonium bromide. Its 1H NMR spectrum is shown in the figure. Figure 3 ,pass Figure 3 As can be seen, the product synthesized in this embodiment has no other impurity peaks and the product has high purity.

[0052] Example 4

[0053] This embodiment provides an electrolyte prepared by the following steps: 2.875 g ZnSO4 and 2.25 g ZnBr2 are dissolved in 10 mL of deionized water, and then 0.366 g of methyltetrahydrothiophene sulfonium bromide prepared in Example 1 is added. The mixture is stirred at room temperature for 12 h to obtain an electrolyte suitable for high-rate aqueous zinc-bromine batteries.

[0054] Example 5

[0055] This embodiment provides an electrolyte prepared by the following steps: 2.875 g ZnSO4 and 2.25 g ZnBr2 are dissolved in 10 mL of deionized water, and then 0.394 g of ethyltetrahydrothiophene sulfonium bromide prepared in Example 2 is added. The mixture is stirred at room temperature for 12 h to obtain an electrolyte suitable for high-rate aqueous zinc-bromine batteries.

[0056] Example 6

[0057] This embodiment provides an electrolyte prepared by the following steps: 2.875 g ZnSO4 and 2.25 g ZnBr2 are dissolved in 10 mL of deionized water, and then 0.422 g of propyltetrahydrothiophene sulfonium bromide prepared in Example 3 is added. The mixture is stirred at room temperature for 12 h to obtain an electrolyte suitable for high-rate aqueous zinc-bromine batteries.

[0058] Example 7

[0059] This embodiment provides a positive electrode sheet, which is prepared by the following steps: 0.6 g of methyltetrahydrothiophene sulfonium bromide prepared in Example 1, 0.2 g of activated carbon, 0.1 g of conductive carbon black, and 0.1 g of CMC are added to 5 mL of deionized water, stirred at room temperature for 48 h, and then coated on a graphite felt with a thickness of 1 mm and dried at 50 ℃ for 3 h to obtain a positive electrode sheet that can be used in high-rate aqueous zinc-bromine batteries.

[0060] Example 8

[0061] This embodiment provides a positive electrode sheet, which is prepared by the following steps: 0.6 g of ethyltetrahydrothiophene sulfonium bromide prepared in Example 2, 0.2 g of activated carbon, 0.1 g of conductive carbon black, and 0.1 g of CMC are added to 5 mL of deionized water, stirred at room temperature for 48 h, and then coated on a graphite felt with a thickness of 1 mm and dried at 50 ℃ for 3 h to obtain a positive electrode sheet that can be used in high-rate aqueous zinc-bromine batteries.

[0062] Example 9

[0063] This embodiment provides a positive electrode sheet, which is prepared by the following steps: 0.6 g of propyltetrahydrothiophene sulfonium bromide prepared in Example 3, 0.2 g of activated carbon, 0.1 g of conductive carbon black, and 0.1 g of CMC are added to 5 mL of deionized water, stirred at room temperature for 48 h, and then coated on a graphite felt with a thickness of 1 mm and dried at 50 ℃ for 3 h to obtain a ring-shaped sulfonium positive electrode sheet that can be used in high-rate aqueous zinc-bromine batteries.

[0064] Example 10

[0065] This embodiment provides a battery comprising 120 μL of electrolyte prepared in Example 4, a ring-shaped sulfonium cathode prepared in Example 7 for use in high-rate aqueous zinc-bromine batteries, a glass fiber separator, 1 μm zinc foil, and a titanium sheet.

[0066] The assembly method is as follows: titanium sheet, zinc foil, glass fiber separator, electrolyte, annular sulfonium positive electrode, and titanium sheet are sequentially placed into a 2016 button cell for coupling to obtain a full cell containing methyltetrahydrothiophene sulfonium bromide.

[0067] Example 11

[0068] This embodiment provides a battery comprising 120 μL of electrolyte prepared in Example 5, a ring-shaped sulfonium cathode prepared in Example 8 for use in high-rate aqueous zinc-bromine batteries, a glass fiber separator, 1 μm zinc foil, and a titanium sheet.

[0069] The assembly method is as follows: titanium sheet, zinc foil, glass fiber separator, electrolyte, annular sulfonium positive electrode, and titanium sheet are sequentially placed into a 2016 button cell for coupling to obtain a full cell containing ethyltetrahydrothiophene sulfonium bromide.

[0070] Example 12

[0071] This embodiment provides a battery comprising 120 μL of electrolyte prepared in Example 6, a ring-shaped sulfonium cathode prepared in Example 9 for use in high-rate aqueous zinc-bromine batteries, a glass fiber separator, 1 μm zinc foil, and a titanium sheet.

[0072] The assembly method is as follows: titanium sheet, zinc foil, glass fiber separator, electrolyte, annular sulfonium positive electrode, and titanium sheet are sequentially placed into a 2016 button cell for coupling to obtain a full cell of propyltetrahydrothiophene sulfonium bromide.

[0073] Comparative Example 1

[0074] This comparative example provides a control electrolyte by dissolving 2.875 g ZnSO4 and 2.25 g ZnBr2 in 10 mL of deionized water and stirring for 12 h to obtain an electrolyte without cyclic sulfonium.

[0075] Comparative Example 2

[0076] This ratio provides a control sample positive electrode. 0.7 g activated carbon, 0.2 g conductive carbon black, and 0.1 g CMC were added to 5 mL of deionized water and stirred for 48 h to obtain a pure carbon positive electrode without cyclic matte.

[0077] Comparative Example 3

[0078] This comparative example provides a battery comprising 120 μL of electrolyte prepared in Comparative Example 1, an annular sulfonium cathode prepared in Example 9 for use in high-rate aqueous zinc-bromine batteries, a glass fiber separator, 1 μm zinc foil, and a titanium sheet.

[0079] The assembly method is as follows: the titanium sheet, zinc foil, glass fiber separator, electrolyte, pure carbon cathode, and titanium sheet are placed into a 2016 button cell and coupled to obtain a full cell without a ring-shaped matte cathode.

[0080] Comparative Example 4

[0081] This comparative example provides a battery comprising 120 μL of the electrolyte prepared in Example 5, a pure carbon cathode prepared in Comparative Example 2, a glass fiber separator, a 1 μm zinc foil, and a titanium sheet.

[0082] The assembly method is as follows: the titanium sheet, zinc foil, glass fiber separator, electrolyte, pure carbon cathode, and titanium sheet are placed into a 2016 button cell and coupled to obtain a full cell without a ring-shaped matte cathode.

[0083] Battery performance test analysis

[0084] The battery from Example 11 was used at a current density of 10–250 mA / cm². 2 The surface capacity is 2 mAh / cm². 2 Electrochemical tests were performed under the specified conditions, and the results are as follows: Figure 4 As shown in the image. It can be seen that the battery operates at 250 mA / cm². 2 It still has a discharge plateau of 1.4 V under the current, which is excellent rate performance.

[0085] The full cells prepared in Examples 10, 11, and 12 were subjected to cyclic voltammetry tests at 0.2 mV / s, as shown below. Figure 5 , Figure 6 , Figure 7 As shown, no additional side reactions occur within the system, the entire zinc-bromine system is relatively clean, and it exhibits good reversibility.

[0086] The full cells prepared in Examples 10, 11, and 12 have a performance of 1 mAh / cm². 2 20 mA / cm 2 The charge-discharge curves under the conditions are as follows: Figure 8 , Figure 9 , Figure 10 As shown, these cyclic sulfonium salts exhibit high coulombic efficiency and low voltage polarization in zinc-bromine full cells, especially ethyltetrahydrothiophene sulfonium bromide at 99.23%.

[0087] The full cells prepared in Examples 10, 11, and 12 have a mAh / cm² content of 1 mAh / cm². 2 20 mA / cm 2 Long-cycle testing was performed under the conditions, and the results were as follows: Figure 11 As shown, the full cell containing ethyltetrahydrothiophene sulfonium bromide exhibits the best performance, maintaining a stable coulombic efficiency of 99.23% after 8000 cycles and demonstrating a long cycle life.

[0088] The full cells prepared in Example 12 and Comparative Examples 3 and 4 have a mAh / cm² content of 1 mAh / cm². 2 20 mA / cm 2 The following is a comparison chart of long-cycle performance: Figure 12 As shown, the system with ethyltetrahydrothiophene bromide added only to the positive electrode exhibited significant coulombic efficiency fluctuations within the first 1500 cycles, subsequently leading to complete battery failure. In contrast, the system with ethyltetrahydrothiophene bromide added only to the electrolyte achieved an average coulombic efficiency of 99.56%, but failed completely after 180 cycles. The system with ethyltetrahydrothiophene bromide added to both the electrolyte and the positive electrode maintained a stable coulombic efficiency of 99.23% throughout an ultra-long cycle life of nearly 9000 cycles, without significant degradation. Therefore, ethyltetrahydrothiophene bromide, as a functional component of both the electrolyte and the positive electrode in zinc-bromine batteries, can improve the shortcomings of traditional systems, such as unstable coulombic efficiency and short cycle life.

[0089] The embodiments of the present invention have been described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions, and variations can be made to these embodiments without departing from the principles and spirit of the present invention, and these variations still fall within the protection scope of the present invention.

Claims

1. A cyclic sulfonium additive that complexes polybrominates, characterized in that, The cyclic sulfonium additive is a cyclic sulfonium bromide salt; it has the general structural formula of Formula 1: ; Formula 1 Wherein: R is one of methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, and decyl.

2. An electrolyte, characterized in that, The cyclic sulfonium additive that complexes polybrominates as described in claim 1.

3. The electrolyte according to claim 2, characterized in that, It also includes soluble zinc salts and water.

4. The electrolyte according to claim 3, characterized in that, The soluble zinc salt is at least one of zinc sulfate, zinc bromide, zinc chloride, zinc nitrate, zinc oxalate, zinc acetate, zinc fluoride, and zinc trifluoromethanesulfonate.

5. The electrolyte according to claim 2, characterized in that, The concentration of cyclic sulfonium bromide salt in the electrolyte is 0.05–0.2 mol / L; the concentration of soluble zinc salt is 0.5–1 mol / L.

6. A positive electrode plate, characterized in that, The cyclic sulfonium additive that complexes polybrominates as described in claim 1.

7. The positive electrode sheet according to claim 6, characterized in that, It also includes conductive carbon and binders; The conductive carbon is at least one of Super P, Ketjen Black, and acetylene black; The adhesive is at least one of carboxymethyl cellulose, polyvinylidene fluoride, and polytetrafluoroethylene.

8. A high-rate aqueous zinc-bromine battery, characterized in that, It includes the electrolyte as described in claim 2, the positive electrode as described in claim 6 or 7, and the negative electrode.

9. A high-rate aqueous zinc-bromine battery according to claim 8, characterized in that, The negative electrode is a zinc metal sheet.